Pattern of Post-Juvenile Moult in Common Snipe (Gallinago Gallinago) and Its Implications for Ageing of the Species - Minias, Piotr; Kaczmarek, Krzysztof; Włodarczyk, Radosław; Janiszewski, Tomasz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2010)
External ageing of Common Snipe (Gallinago gallinago) still engenders considerable problems. To improve precision of age determination on the basis of plumage characteristics a scheme of post-juvenile moult was investigated in approximately 1200 first-year Common Snipes caught during autumn migration in central Poland. Post-juvenile moult was commenced from body feathers followed by moult of rectrices, lesser/median wing coverts and tertials. Moult sequence showed high inter-individual variability and was started in rectrices (36.9%), wing coverts (25.3%), tertials (8.4%) or simultaneously in several of these tracts of feathers (29.4%). Moult of rectrices was finished before completion of moult of wing coverts and tertials. Moult of tertials finished as the last from all age-indicative tracts of feathers. Consequently, tertials were suggested as the most useful for ageing of first-year Common Snipes in an advanced stage of moult. There was no case of moult of the outermost tertial in first-year birds. The second tertial from distal side of wing was moulted as the last one within this tract of feathers and thereby should be of special interest during plumage examination.